On the spread of social protection systems - Peter Egger; Doina Maria Radulescu; Nora Strecker (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper undertakes an empirical analysis of the adoption of various components of social security systems as well as contribution rates. Apart from economic determinants of the adoption, the empirical analysis features determinants relating to countries' political systems and contagion. We analyse to which extent a country's integration into the international network of economic and political cooperation, the similarity of political systems, and economic interdependence facilitate the adoption of social security system components between economies. We study the heterogeneous responses of high and middle to low income economies to country-specific as well as foreign countries' fundamentals.
Keywords: H55; H2; C22; F42; 330; social security systems; taxation; international comparisons; panel data analysis; principal component analysis